Attitudes and barriers to the use of the World Health Organisation’s surgical safety checklist at a specialized academic hospital in the Western Cape, South Africa - Davids, Vanessa Berenice (Stellenbosch : Stellenbosch University, 2023)
Thesis (MNur)--Stellenbosch University, 2023.